Taxonomic review of the Agrisius guttivitta Walker species group with transfer of the genus Agrisius Walker to the family Nolidae Bruand and descriptions of five new species (Lepidoptera: Nolidae: Eligminae) - Volynkin, Anton V.; Saldaitis, Aidas (Zootaxa, 2022)
The genus Agrisius Walker, 1855 is transferred from the family Erebidae, subfamily Arctiinae to the family Nolidae, subfamily Eligminae. The Agrisius guttivitta Walker species group is reviewed and five new species are described: Agrisius soror sp. n. (North Vietnam), Agrisius witti sp. n. (China, Yunnan), Agrisius cernyi sp. n. (North and West Thailand), Agrisius kachina sp. n. (North Myanmar), and Agrisius frater sp. n. (China, Shaanxi). A new synonymy is introduced: Agrisius vernalis Dubatolov, Kishida & Wang, 2012 = Agrisius fangchenglaiae Orhant, 2015, syn. n. Adults and male and female genitalia are illustrated.